Вклад кафедры тифлопедагогики в разработку проблем теории и практики образования лиц с нарушениями зрения в Украине - Федоренко, С. В.; Федоренко, И. В.
In the article the hist ory of the methodological and scientifi cresearch work of the department of tyfl opedagogic, marked by modern researchers contribute to the theory and practice of training and development of people with visual impairments.
Keywords: Образование